2023
DOI: 10.3390/ph16020285
|View full text |Cite|
|
Sign up to set email alerts
|

Therapeutic Potential of Zeolites/Vitamin B12 Nanocomposite on Complete Freund’s Adjuvant-Induced Arthritis as a Bone Disorder: In Vivo Study and Bio-Molecular Investigations

Abstract: Rheumatoid arthritis (RA) is a long-term autoimmune disease. As nanotechnology has advanced, a growing number of nanodrugs have been used in the treatment of RA due to their unique physical and chemical properties. The purpose of this study was to assess the therapeutic potential of a novel zeolite/vitamin B12 nanocomposite (Nano ZT/Vit B12) formulation in complete Freund’s adjuvant (CFA)-induced arthritis. The newly synthesized Nano ZT/Vit B12 was fully characterized using various techniques such as XRD, FT-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 67 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…According to the findings of the present study, it was observed that a majority of patients diagnosed with RA utilize systemic immunosuppressive or steroid medications [ 21 ]. Furthermore, research has indicated a potential correlation between the utilization of systemic immunosuppressants or steroids and the heightened risk of developing CC.…”
Section: Discussionmentioning
confidence: 83%
“…According to the findings of the present study, it was observed that a majority of patients diagnosed with RA utilize systemic immunosuppressive or steroid medications [ 21 ]. Furthermore, research has indicated a potential correlation between the utilization of systemic immunosuppressants or steroids and the heightened risk of developing CC.…”
Section: Discussionmentioning
confidence: 83%